Socioeconomic position in childhood and cognitive aging in Europe - Cermakova, Pavla; Formanek, Tomas; Kagstrom, Anna; Winkler, Petr (Neurology, 2018)
OBJECTIVES: We aimed to investigate whether socioeconomic position (SEP) in childhood has an effect on the level of cognitive performance and the rate of cognitive decline in older adults. METHODS: We performed a prospective cohort study of individuals enrolled in a multicenter population-based study, SHARE (Survey of Health, Ageing and Retirement in Europe). Interviews were conducted in 6 waves at approximately 2-year intervals and included examinations of cognitive performance (memory, verbal fluency, delayed recall) and measurements of childhood SEP (participants' household characteristics at the age of 10 years). We estimated the associations of SEP with the level of cognitive performance using linear regression and the relation to the rate of cognitive decline with mixed-effects models. RESULTS: This study included 20,244 participants from 16 European countries (median age at baseline 71 years, 54% women). Adverse childhood SEP was associated with a lower level of baseline cognitive performance. This association was attenuated after adjustment for clinical and social risk factors but remained statistically significant. Childhood SEP was not related to the rate of cognitive decline. CONCLUSIONS: Variation in childhood SEP helps to explain differences in cognitive performance between older people, but not the rate of decline from their previous level of cognition. Strategies to protect cognitive aging should be applied early in life.
Keywords: společenská třída; senioři; senioři nad 80 let; Neuropsychological Tests; zranitelné populace; Europe; Cognitive Aging; Cohort Studies; Social Class; kognitivní stárnutí; Evropa; Cognition Disorders; mužské pohlaví; samostatný způsob života; kohortové studie; kognitivní poruchy; Aged, 80 and over; ženské pohlaví; neuropsychologické testy; Humans; Vulnerable Populations; Independent Living; Female; Aged; lidé; Male